PENGARUH UKURAN PERUSAHAAN, TINGKAT HUTANG, ARUS KAS OPERASI, AKRUAL TERHADAP PERSISTENSI LABA (Study Empiris Perusahaan Properti dan Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2018-2020) - fitri nuraini; Zeni Utami (.Universitas PGRI Adi Buana, 2022)
Financial statements can be used as information by investors in making investment decisions. In the financial statements there are profits that can determine performance, so a company must have earnings quality used to predict future earnings. This research is a quantitative research. Collecting data in the form of secondary data, namely financial statements. The population of this study are 61 Property and Real Estate Companies Listed on the Indonesia Stock Exchange. Sampling using purposive sampling method, to obtain 20 companies in 3 years of observation as much as 60 data used by researchers. Based on the results of the study, it shows that the size of the company and the level of debt have a partial effect on earnings persistence with a negative relationship with significant values ​​of 0.046 and 0.000. Besides, operating cash flow has a partial effect on earnings persistence with a positive direction with a significant value of 0.009 and accruals have no partial effect on earnings persistence with a positive direction relationship with a significant value of 0.207. Firm size, debt level, operating cash flow, accruals have a simultaneous effect on earnings persistence with a significant value of 0.000.